The Utilization of Digital Marketing and Entrepreneurial Skills in Enhancing Business Success for MSMEs in Bogor City - Yanita Ella Nilla Chandra; Risya Zahrotul Firdaus; Syamsurizal Syamsurizal; Riskon Ginting; Rizka Sakinah; Dewi Rakhmawati (University of Merdeka Malang, 2023)
Indonesia hosts a substantial number of micro, small, and medium enterprises (UMKM), comprising around 99.99% (65.5 million units) of businesses in 2018, as stated by the Ministry of Cooperatives and SMEs. Despite their micro classification, these enterprises play a significant role, contributing about 89.2% to Indonesia's workforce and making vital economic contributions. However, 5.9% of businesses still feel the positive impacts of Covid-19. Among them, resilient businesses (5.9%) adapt by expanding marketing channels, with social media networks being a key strategy for digital marketing communication. To assess the impact of digital marketing and entrepreneurial skills on UMKM success in Bogor City, this study employed a quantitative approach. The questionnaire-based research involved 100 randomly selected participants from a population of 3,845 UMKM business players in Bogor City. Using PLS-SEM analysis, the research scrutinized the integrated framework required for this strategy. Notably, Bogor City, facing a 60% UMKM income decline during the pandemic, served as a focal point. The study utilizes SEM methodology within an explanatory research design to explore the dynamics of UMKM success in the face of contemporary challenges.